(untitled) (World Bulletin of Public Health, 2023)
The study aimed to follow up the treatments added to the fat of poultry slaughterhouse and their impact on improving some productive performance and some meat characteristics in male Awassi lambs, the weight of the animals was recorded weekly for the duration of the study (120 days), all lambs were slaughtered, skinned and hollowed until the end of the study period and the results were as follows: where the treatments T3 and T4 outperformed a high significant superiority